کشمیر: جغرافیہ، ثقافت، معاشرت اور قدرتی حسن کا تحقیقی جائزہ: Kashmir: A Critical Study of Geography, Culture, Society, and Natural Beauty (Al-Aasar, 2025)
Kashmir, often referred to as the “Paradise on Earth,” is renowned for its breathtaking landscapes, cultural richness, and diverse society. This study provides a comprehensive analysis of Kashmir’s geography, climate, and natural beauty, highlighting its lush gardens, flowing streams, orchards, and architectural marvels. Beyond its physical charm, Kashmir is a melting pot of cultures, languages, and religions, reflecting a unique social fabric that has evolved over centuries. The research examines the historical and contemporary significance of Kashmir’s cultural practices, festivals, and social norms, illustrating how these elements contribute to the region’s identity. Attention is given to the traditional livelihoods, local crafts, and agricultural practices, especially the cultivation of famous fruits and the management of gardens. Furthermore, the study addresses the impact of modern challenges, such as urbanization and socio-political changes, on Kashmir’s environment and cultural heritage. By integrating geographical, social, and cultural perspectives, this paper seeks to provide a holistic understanding of Kashmir, emphasizing the need for preserving its natural beauty, heritage, and communal harmony. The findings highlight that the appreciation and protection of Kashmir’s physical and cultural resources are not only vital for environmental sustainability but also for maintaining social cohesion and fostering pride in regional identity. This research serves as a resource for scholars, policymakers, and anyone interested in understanding the multidimensional aspects of Kashmir.